Effects of Carbonization Temperature and Time during Carbon Riveting Process on the Stability of Pt/C Catalyst. Issue 4 (18th August 2014) - Jiang, Z.‐Z.; Wang, Z.‐B.; Rivera, H.; Qu, W.‐L.; Gu, D.‐M.
Abstract Effects of carbonization temperature and time during carbon riveting process on the stability of Pt/C catalysts have been investigated systematically. X‐ray diffraction, transmission electron microscopy, cyclic voltammograms, and accelerated potential cycling tests have been performed to characterize the catalysts. The experimental results show that the activity of the riveted Pt/C catalyst decreases with the increasing of the heat‐treated temperature and the extension of heat‐treated time due to sintering of Pt nanoparticles. The stability of the carbon riveted Pt/C catalysts exhibits the increasing trend with the increase of the carbonization time and temperature. Considering both of the activity and stability of the riveted Pt/C catalysts, the optimized carbonization temperature and time are 400 °C and 60 min for a Pt/VulcanXC‐72 catalyst with starting particle size before carbonization of 2.2 nm and 20 wt% platinum loading, respectively.